Prognostic role of interim F-18 fluorodeoxyglucose positron emission tomography-computed tomography during chemoradiation therapy in patients with hypopharyngeal squamous cell carcinoma - Takamitsu Mase; Yutaka Toyomasu; Hajime Ishinaga; Yui Nanpei; Tomoko Kawamura; Akinori Takada; Yasutaka Ichikawa; Noriko Ii; Tomoya Hirata; Kazuhiko Takeuchi; Hajime Sakuma; Yoshihito Nomoto (PLoS ONE, 2026)
This study aimed to investigate the usefulness of interim 18 F fluorodeoxyglucose positron emission tomography–computed tomography (FDG PET/CT) during definitive radiation therapy (RT) as a prognostic indicator of disease recurrence in patients with hypopharyngeal squamous cell carcinoma. This prospective analysis included 35 patients with biopsy-proven hypopharyngeal squamous cell carcinoma who received platinum-based chemoradiotherapy and underwent pretreatment FDG PET/CT and interim FDG PET/CT (iPET) at a cumulative RT doses of 36.0–45.0 Gy. The maximum standardized uptake value (SUVmax), metabolic tumor volume, and total lesion glycolysis of the primary tumor (PT) and combined total lymph nodes for both pre-PET and iPET were analyzed, and their percentage reductions in iPET were calculated. The optimal cutoff values of the metabolic parameters were derived from receiver operating characteristic curves. The outcomes were compared between patients with metabolic parameters above and below the respective cutoff values. Disease recurrence (locoregional or distant) was defined as a biopsy-proven tumor or unequivocal clinical and radiological evidence of progression. Twelve (34%) patients experienced disease recurrence during a median follow-up of 52 months. Univariate Cox regression analysis revealed that the reduction ratio of the SUVmax of the PT (ΔSUVp; hazard ratio, 7.685; p = 0.008) was a significant predictor of disease recurrence. Kaplan–Meier curve analysis revealed that a smaller ΔSUVp was associated with worse progression-free survival (log-rank, p = 0.002). Metabolic parameters measured using iPET may be useful predictors of disease recurrence in patients with hypopharyngeal squamous cell carcinoma treated with chemoradiotherapy. In this study, ΔSUVp was the best prognostic indicator.